Development, Standardization, and Acceptability of Cassava (manihot esculenta) – Okara Polvoron enhanced with Malunggay (moringa oleifera) - Bagnes, Elaine; Quinatadcan, Jose; Sibi, Roy; Balagtas, Maribel; Estrada, Miriam; Laborde, Gladys Mae; Oasan, Ruchel (8ISC Abstract Proceedings, 2022)
Cassava and malunggay are economical and nutritious crops in the Philippines which are not popular among younger people, and okara (soypup) is a byproduct of soy milk and tokwa production that is commonly thrown away thus, the development of the product. The study utilized experimental research design through trial formulation and has used percentages to determine the acceptability of the product. The purpose of this food research was to utilize locally available foods and utilize food waste. Cassava, soy pulp, and malunggay were dehydrated and ground separately. Pulverized cassava and soy pulp which are the main ingredients, were toasted. After toasting, malunggay the nutrient enhancer, grounded baked peanut used for a crunchy mouthfeel, muscovado sugar used as sweetener, milk as a taste enhancer and a protein source, and margarine as a binder were mixed thoroughly with the toasted cassava and okara. The product is a high source of thiamine (B1), a good source of riboflavin (B2) and calcium, and it is liked by 89% of evaluators. The product’s shelf life is 30 days at room temperature, and each piece of 15 grams is 4.50 pesos. It is recommended that the product be produced for commercial purposes and further experiment to increase the shelf life. Keywords : okara, malunggay, polvoron, cassava